(untitled) (Journal of Chittagong Medical College Teachers’ Association, 2018)
Background : Anterior Cervical Discectomy and Fusion (ACDF) is widely performed for cervical degenerative disease with autograft or allograft with long term satisfactory outcome. But the complications of autogenous bone grafting cause the spinal surgeons to seek alternative method. This prospective study was conducted to observe the outcome of using stand-alone titanium cage in ACDF. Materials and methods : Total 50 patients (68 levels) with degenerative compressive cervical myelorediculopathy were operated using stand-alone titanium cage from July 2013 to June 2015 in the Department of Neurosurgery, Chittagong Medical College Hospital. All patients were examined and evaluated preoperatively by plain X-ray and MRI and postoperatively by plain X-ray at one, three and 12 months. Clinical and neurological outcome was assessed by Japanese Orthopedic Association (JOA) score. Results: The mean age was 42.04±7.94 years ranged from 30 to 66 years. Maximum patients were in 41-50 years age group. Quadriparesis was found most common symptom (60%) followed by brachialgia (20%). Out of 50 patients, 32 (64%) suffered from single level compression while 18 (36%) patients suffered from two level compression. Among all operated levels, C5-6 (n-30, 44.2%) was most common level followed by C6-7 (n- 20,29.4%) and C4-5 (n-12, 17.6%) level. All patients improved in terms of their neck pain, redicular arm pain, clumsy hand movement and quadriparesis after surgery. Subsidence was observed in 15 (30%) patients and kyphosis was observed in 10 (20%) patients. All patients with subsidence and kyphosis were neurologically stable and no revision was required. Mean preoperative JOA score was 8.38±3.71 and mean post operative JOA score was 12.92±3.39. Among all patients in post operative follow up, 22 (44%) patients showed excellent recovery and 15 (30%) patients showed good recovery. Conclusion: Anterior cervical fusion using a stand-alone titanium cage is a safe and effective procedure allowing excellent to good functional recovery and avoiding donor site morbidity. Titanium cage can be an effective alternative to iliac bone autograft. JCMCTA 2017 ; 28 (2) : 34-38